O2-S4.02 Cost-effectiveness of screening for Chlamydia trachomatis in Dutch pregnant women. (10th July 2011) - Rours, G I J G; Verkooijen, R P; Verbrugh, H A; Postma, M J
Abstract : Background: Chlamydia trachomatis infections may have serious consequences for women, their offspring and pregnancy outcomes, but are largely asymptomatic. Prevention is therefore based on screening. Screening for Chlamydial infections during pregnancy is not part of routine antenatal care in many countries, as in the Netherlands. Objective: Cost-effectiveness analysis of C trachomatis screening during pregnancy. Methods: A health-economic decision analysis model was designed, which included not only potential health outcomes of C trachomatis infection for women, partners and infants, but included also premature delivery. The cost-effectiveness was estimated from a societal perspective using recent prevalence data from a population-based prospective cohort study among pregnant women in the Netherlands. The prevented costs were calculated by linking health outcomes with health care costs and productivity losses. Cost-effectiveness was expressed as net costs per major outcome prevented and was estimated in a base-case analysis as well as a sensitivity- and scenario analysis. Results: In the base-case analysis (current base-case test cost €12), the costs to detect 1000 pregnant women with C trachomatis were estimated at €378 300. Cost savings on complications were estimated at €924 600 resulting in net cost savings. Sensitivity analysis showed that net cost savings remained for a broad range of variation in underlying assumptions such as test costs (up to €32), proportion of complications that can be averted (between 25% and 75%), risk for PID (0.4% to 40%), and any other parameter within plausible ranges (between + to −25%). Cost savings were most sensitive to preterm delivery, but remained when preterm delivery was excluded (making the model comparable to other cost-effectiveness analyses). Scenario analysis showed even more cost savings with targeted screening for women's age (≥20 years, 26–30 years, and <30 years) or pregnancy rate (first pregnancies only). At base-case costs, screening appeared cost-saving in populations with a chlamydial prevalence beyond 1.7%. At the extremes, with test costs as low as €5 cost savings would already occur beyond a prevalence of 0.6% and with test costs as high as €40 cost savings would occur beyond a prevalence of 4.7% see Abstract O2-S4.02 figure 1 . Conclusions: C trachomatis screening of pregnant women in the Netherlands is cost-saving.